The polemics between Heraclitus and Hesiod - Vieira, Celso (2013)
The article attempts to verify how Heraclitus uses the traditional ideas expressed in Hesiod’s poems as a counter-example of his conception of how the world works. First the role of the poet as someone who learns from tradition and teaches in order to reinforce traditional knowledge is investigated. Fragments B57 and B106 present the problem. Day and night serve as paradigms. Hesiod presents them as two separated phenomena and qualifies some as good and others as bad. Heraclitus refutes such a view in an attempt to demonstrate not only that they are opposites united by a diachronic change of the day turning into night and the other way but also how it is a human mistake to try to qualify them as good or bad.